(untitled) (Global Journals of Research in Engineering, 2024)
This work is devoted to the development of the engineering seismic monitoring method created in GS RAS In previous years the method of standing waves was created and put into practice It helps to separate natural oscillation modes of buildings and other engineering structures The natural oscillations of hundreds of various objects buildings bridges dams etc had been studied and identified We assumed that the physical condition of studied constructions could be controlled during exploitation by measuring the changes of natural oscillation frequencies That would help to identify the appearance of defects in constructions to prevent the risk of their destruction However it turned out that not everything is that simple changes in frequency values are logically affected by changes in the environment around the studied objects This article provides examples of these relations influence of changes in environmental temperature mass of objects and precipitation on the frequencies of natural oscillations